Electron transfer within 2,7-dinitronaphthalene radical anion - Clark, Timothy; et al. (Journal of the American Chemical Society, 2004)
The optical spectrum of 2,7-dinitronaphthalene radical anion generated by Na(Hg) reduction in acetonitrile containing a large excess of cryptand[2.2.2] exhibits a Hush-type intervalence charge-transfer band at 1070 nm, estimated to correspond to an off-diagonal matrix coupling element of 310 cm(-1). The interpolated rate constant for intramolecular electron transfer at 293 K measured by ESR between 225 and 320 K for this solution is 3.1(+/-0.2) x 10(9) s(-1). Rate constants estimated in two ways from the optical parameters using the Marcus-Hush assumption that the diabatic surfaces should be parabolae are 1.0 and 0.11 x 10(9) s(-1), and those using diabatic surfaces that fit the observed charge-transfer band are 9.6 and 3.4 x 10(9) s(-1), when used with an electron-transfer distance on the adiabatic surfaces of 6.42 A. Similar measurements and comparisons were also carried out using dimethylformamide and butyronitrile as solvents. The success of simple, classical two-state Marcus-Hush theory precludes an electron-hopping mechanism. UHF calculations predict a planar unsymmetrical gas-phase structure for 1,3-dinitrobenzene radical anion but give serious spin contamination. Semiempirical AM1 calculations using singles excitation configuration interaction with an active space of 70 orbitals and the COSMO solvent model also give a planar unsymmetrical structure. These calculations make the internal vibrational component of the reorganization energy nearly constant, and much smaller than the solvent reorganizational component, and predict the transition energy to lie between that observed in acetonitrile (9360 cm(-1)) and those observed in dimethylformamide (8100 cm(-1)) and butyronitrile (8040 cm(-1)).